Single center, open label dose escalating trial evaluating once weekly oral ixazomib in ART-suppressed, HIV positive adults and effects on HIV reservoir size in vivo. (December 2021) - Cummins, Nathan W; Baker, Jason; Chakraborty, Rana; Dean, Patrick G; Garcia-Rivera, Enrique; Krogman, Ashton; Kumar, Shaji; Kuzmichev, Yury V; Laird, Gregory M; Landay, Alan; Lichterfeld, Mathias; Mahmood, Maryam; et al.
Abstract: Background: Achieving a functional or sterilizing cure for HIV will require identification of therapeutic interventions that reduce HIV reservoir size in infected individuals. Proteasome inhibitors, such as ixazomib, impact multiple aspects of HIV biology including latency, transcription initiation, viral replication, and infected cell killing through the HIV protease – Casp8p41 pathway, resulting in latency reversal and reduced measures of HIV reservoir size ex vivo. Methods: We conducted a phase 1b/2a dose escalating, open label trial of weekly oral ixazomib for 24 weeks in antiretroviral (ART)-suppressed, HIV positive adults (NCT02946047). The study was conducted from March 2017 to August 2019 at two tertiary referral centers in the United States. The primary outcomes were safety and tolerability of oral ixazomib. Secondary outcomes included changes in immunologic markers and estimates of HIV reservoir size after ixazomib treatment. Findings: Sixteen participants completed the study. Ixazomib up to 4mg weekly was safe and well-tolerated, yielding no treatment-emergent events above grade 1. In exploratory analyses, ixazomib treatment was associated with detectable viremia that was below the lower limit of quantification (LLQ) in 9 participants, and viremia that was above LLQ in 4 of 16 participants. While treatment was associated with reduced CD4 counts [baseline 783 cells/ mm 3 vs. week-24 724 cells/ mm 3 p=0.003], there were no changes in markers of cellular activation, exhaustion or inflammation. Total HIV DNA and proviral sequencing were not altered by ixazomib treatment. Intact proviral DNA assay (IPDA) identified intact proviruses in 14 patients pre-treatment, and in 10/14 of those subjects post treatment values were reduced (P=0.068), allowing a calculated intact proviral half life of 0.6 years (95% CI 0.3, 2.5), compared to 7.1 years (95% CI 3.9, 18, p=0.004) in historical controls. Differentiation Quantitative Viral Outgrowth Assays (dQVOA) identified measurable proviruses in 15 subjects pre-treatment; post-treatment values were numerically reduced in 9, but overall differences were not significantly different. Interpretation: Our study successfully met its primary endpoint of demonstrating the safety of ixazomib for 24 weeks in HIV infected persons. Exploratory analyses suggest that the effects observed ex vivo of latency reversal and reductions in HIV reservoir size, also occur in vivo. Future controlled studies of ixazomib are warranted. Funding: This study was funded by Millennium Pharmaceuticals Inc..; the Mayo Clinic Foundation; the National Institutes of Health, including the National Institute of Allergy and Infectious Diseases, Division of AIDS, the National Heart, Lung and Blood Institute, the National Institute of Diabetes and Digestive and Kidney Diseases, the National Institute of Neurological Disorders and Stroke, and the National Institute on Drug Abuse. Mayo Clinic also acknowledges generous funding support from Mr. Joseph T. and Mrs. Michele P. Betten.